1999
DOI: 10.1002/(sici)1521-3773(19990802)38:15<2203::aid-anie2203>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

A Convergent Strategy for the Modification of Peptide Nucleic Acids: Novel Mismatch-Specific PNA-Hybridization Probes

Abstract: Coupling of nonnatural nucleobases to the orthogonally protected backbone 1 on the solid phase provided access to novel peptide nucleic acid (PNA) conjugates 2, which are difficult to synthesize by standard routes. Hybridization probes containing the thiazolorange dye might allow DNA sequence analysis in real time. B-CH(2)CO=modified nucleobase, fluorescent dye, etc; Boc, Fmoc=protecting groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 4 publications
1
51
0
2
Order By: Relevance
“…1C). 11,12 These two approaches represent a later stage of modified base introduction, as compared with approach A, and can be labor and material saving in their execution.…”
Section: +mentioning
confidence: 99%
“…1C). 11,12 These two approaches represent a later stage of modified base introduction, as compared with approach A, and can be labor and material saving in their execution.…”
Section: +mentioning
confidence: 99%
“…[10] A particularly attractive feature is that PNAs are not subject to nuclease or protease mediated degradation and are thus highly stable even in living cells. These properties have been advantageously employed for example in pre-gel hybridisations as alternative to Southern hybridisation, [11] for the identification of point mutations by PCR clamping [12,13] and fluorescently labelled probes, [14,15] in the fabrication and usage of PNA probe arrays, [16] and in the isolation, [17] blocking [18±21] and restriction [22±24] of genes or mRNAs. For applications as diagnostical probes PNAs as well as oligonucleotides have to be equipped with reporter groups.…”
Section: Introductionmentioning
confidence: 99%
“…It is the aim of the work presented in here to extend the repertoire of the existing methodology available for PNA labelling. It will be shown that the attachment of fluorophores to the C-terminus [28] and to internal conjugation sites [15] is possible by employing convergent strategies and both solution-and solid-phase labelling of PNA will be discussed. Focus of these studies is the rapid synthesis of dual labelled PNA probes [29,30] which may prove suitable for the sequence specific DNA-detection in homogeneous solution.…”
Section: Introductionmentioning
confidence: 99%
“…We reckoned that, due to this inter-or intramolecular association, a fluorescence-donor and a fluorescence-quencher group appended to the unhybridized PNA molecule 1 would be positioned in close proximity ( Figure 1). [7] In analogy to the DNA-based molecular beacons 2, which were introduced by the pioneering work of Kramer and Tyagi, collisional quenching and the distance-dependent fluorescence resonance energy transfer (FRET) would diminish the fluorescence of the donor label. [8a] Hybridization with complementary nucleic acids should induce a structural reorgan- [9] The binding affinity is defined as K a [complex]/([sugar] [cation]).…”
mentioning
confidence: 99%